Eaton uses additive manufacturing to produce parts for jet trainer aircraft. Issue 7 (July 2019) - Atkinson, Simon
Abstract : Power management company Eaton is using additive manufacturing (3D printing) to produce parts for an aerospace company based in Taiwan for use in a jet trainer aircraft. The use of this technology has a number of benefits, including eliminating potential leak paths and reducing component development time and weight.